2022
DOI: 10.3389/fpubh.2022.977453
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional prevalence of disabilities among children and adolescents: Analysis of findings from global health databases

Abstract: ObjectiveThe United Nations' Sustainable Development Goals (SDGs) require population-based data on children with disabilities to inform global policies and intervention programs. We set out to compare the prevalence estimates of disabilities among children and adolescents younger than 20 years as reported by the world's leading organizations for global health statistics.MethodsWe purposively searched the disability reports and databases of the United Nations Children's Fund (UNICEF), the World Health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…It is estimated that over 15% of the world’s population—with up to 190 million (3.8%) of this specific demographic who are aged 15 and older experiencing serious functional challenges—frequently require health care facilities [ 2 ]. On the basis of household surveys carried out on child functional status, the United Nations International Children’s Emergency Fund (UNICEF) estimated that 28.9 million (4.3%) 0–4-year-olds, 207.4 million (12.5%) 5–17-year-olds, and 236.4 million (10%) 0–17-year-olds had moderate-to-severe impairments [ 3 ]. On the other hand, the Global Burden of Disease (GBD) 2019 reported estimates of 49.8 million (7.5%) children who were less than 5 years old, 241.5 million (12.6%) children between 5–19 years, and 291.3 million (11.3%) children younger than 20 years old to all have mild-to-severe impairments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over 15% of the world’s population—with up to 190 million (3.8%) of this specific demographic who are aged 15 and older experiencing serious functional challenges—frequently require health care facilities [ 2 ]. On the basis of household surveys carried out on child functional status, the United Nations International Children’s Emergency Fund (UNICEF) estimated that 28.9 million (4.3%) 0–4-year-olds, 207.4 million (12.5%) 5–17-year-olds, and 236.4 million (10%) 0–17-year-olds had moderate-to-severe impairments [ 3 ]. On the other hand, the Global Burden of Disease (GBD) 2019 reported estimates of 49.8 million (7.5%) children who were less than 5 years old, 241.5 million (12.6%) children between 5–19 years, and 291.3 million (11.3%) children younger than 20 years old to all have mild-to-severe impairments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These women, children and families lack healthcare access and are more vulnerable to toxic stressors beginning before conception. Data from the National Health Interview Survey reported increasing prevalence of DD among US children aged 3–17 years between 2009–2017 [ 79 ], following similar worldwide trends as reported using functional or statistical models in LMIC [ 80 ]. Increasing numbers of children with DD emphasize the need for a bio-social model of care that advocates for healthcare beginning before the first 1000 days for the most vulnerable women and children in both LMIC and HICMD.…”
Section: Healthcare Delivery For Children With Ddmentioning
confidence: 80%
“…The GBD Study from IHME ( https://vizhub.healthdata.org/gbd-results/ ) is presently the only global health database that provides global, regional, and national prevalence estimates of specific disabilities among children and adolescents according to the American Psychiatric Association's (APA's) Diagnostic and Statistical Manual of Mental Disorders (DSM) ( 17 ), or WHO's International Classification of Diseases (ICD) codes ( 18 ). The selection of specific disabilities for our umbrella review was therefore guided by those typically reported by GBD database to facilitate appropriate comparability ( 3 ). These disabilities include attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (or simply “autism” hereinafter), cerebral palsy, developmental intellectual disability, epilepsy, hearing loss and vision loss.…”
Section: Methodsmentioning
confidence: 99%
“…The United Nations' Sustainable Development Goals (SDGs) are widely embraced, especially in low- and middle-income countries (LMICs), as the priority global agenda for improving population health and well-being by 2030 ( 1 ). The disability-inclusive provisions of the SDGs have stimulated a growing interest in children and adolescents (hereinafter reported as “children”) with developmental disabilities globally ( 2 , 3 ). The Convention on the Rights of Persons with Disabilities (CRPD) defines persons with disabilities to include “those who have long-term physical, mental, intellectual or sensory impairments which in interaction with various barriers may hinder their full and effective participation in society on an equal basis with others” ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation